PERBANDINGAN PENYULUHAN CARA MENYIKAT GIGI TERHADAP PENURUNAN NILAI DEBRIS INDEX MENGGUNAKAN MEDIA VIDEO DENGAN MEDIA PHANTOM PADA MURID SDN 2 HAJIMENA LAMPUNG SELATAN TAHUN 2020 - Arianto Arianto; Karsal Meilendra (Jurnal Kesehatan Gigi, 2021)
Maintaining dental and oral hygiene by brushing teeth at the right time has not become a habit of Indonesian society. To make people aware of health, it is necessary to do health socialization by conducting counseling. In the process of delivering material to the target, the selection of the right media and methods is very helpful in achieving efforts to change people's behavior. Media is a component in extension. Video media and phantom media are media that can be used in health education. The purpose of counseling is to get a more perfect understanding, namely by seeing, listening, demonstrating and demonstrating to the target audience a process with correct procedures, for example by showing how to brush teeth properly and correctly.The purpose of this study was to determine the comparison of counseling on how to brush teeth to decrease the value of the debris index using video media with phantom media for students of SDN 2 Hajimena South Lampung in 2020. This type of research is a quasi experiment. This research method used pre-experimental with one group pre and posttest design approach. The research was conducted at SDN 2 Hajimena Natar South Lampung. The population in this study were all students of SDN 2 Hajimena Natar South Lampung for grades IV, V and grade VI in 2020, totaling 112 people. The sample in this study were 112 people. The variables used in this research are Vedio Media, Demonstration Method and Debris Index. The results of the T-test resulted in P value = 0.043. The results of this analysis showed that there was a difference between counseling using video media and phantom media.